MATH ADVENTURE BOARD UNTUK MENINGKATKAN PEMAHAMAN OPERASI HITUNG BILANGAN CACAH - Tsamrotul Ihtiari, Dhiya Ayu (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
Difficulties in understanding addition and subtraction operations with whole numbers remain a challenge for early elementary school students. One of the main causes is the lack of engaging and interactive learning media. This study aims to analyze the effectiveness of using the Math Adventure Board in enhancing students' understanding of addition and subtraction operations with whole numbers. This research employed a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 17 randomly selected first-grade students from MIN 3 Purworejo. Data were collected through validated pretest and posttest assessments. The analysis results showed that the obtained gain score was 0.67 (moderate category), and the paired t-test indicated a significant difference between the pretest and posttest results with a p-value < 0.05. These findings suggest that the Math Adventure Board effectively improves students' understanding of addition and subtraction operations with whole numbers. Therefore, this media can be considered an alternative and effective mathematical learning strategy at the elementary school level. Keywords: Math Adventure Board, whole number operations, interactive learning, conceptual understanding